2007
DOI: 10.1002/crat.200711052
|View full text |Cite
|
Sign up to set email alerts
|

Vapor phase growth of GaN using GaN powder sources and thermogravimetric investigations of the evaporating behaviour of the source material

Abstract: The growth of GaN from the vapor phase is a promising technique for producing both bulk GaN crystals and GaN layers. For establishing a growth method from the vapor phase the source material and reactor setup are of great importance. Highly pure and self synthesized GaN powder was chosen as source material. The evaporation behaviour of the GaN powder was studied by means of thermogravimetry (TG). A vertical growth reactor was set up according to the results of numerical simulations of the temperature distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Furthermore, there is ample evidence that liquid Ga catalyzes the decomposition of GaN [5][6][7][8][9]. In fact, in their study, Pisch and Schmidt-Fetzer [6] showed that the rate-limiting step for the decomposition of GaN is the formation of liquid Ga.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is ample evidence that liquid Ga catalyzes the decomposition of GaN [5][6][7][8][9]. In fact, in their study, Pisch and Schmidt-Fetzer [6] showed that the rate-limiting step for the decomposition of GaN is the formation of liquid Ga.…”
Section: Discussionmentioning
confidence: 99%
“…At the very beginning the low‐pressure solution growth (LPSG) technique and the sublimation method were developed at IISB to evaluate whether these crystal growth techniques would have the potential to serve as industrial production methods for growing GaN bulk crystals. Very quickly it became clear, that the sublimation method is not suitable for such purpose as the GaN powder decomposes incongruently, such that only liquid Ga remains after a short period of time and additional transport agents would then be needed to control the transport of Ga species from the source to the growth interface . Therefore, no principal advantage exists compared to the mostly used hydride vapor phase epitaxy (HVPE) technique.…”
Section: Development Of Wide Bandgap Semiconductors (Sic Gan Aln)—cmentioning
confidence: 99%
“…Сублимационный 6 рост (также -конденсация из паровой фазы, модифицированный метод Леви), разработанный Ю. М. Таировым и В. Ф. Цветковым [66], используется для получения кристаллов SiC и AlN [41,67,68,69], ZnO [70], волокон AlN [71], других нитридов, например, нитрида титана [72]. Сублимационный рост кристаллов GaN менее успешен [73] равновесное давление азота над поверхностью GaN на шесть порядков выше, чем над AlN [74].…”
Section: Introductionunclassified